PERCEPTION AND DEPICTION OF BASIC COLOR RELATIONSHIPS IN PAINTING PERFORMANCE - Oybek Norkulovich Shomurodov (Scholar Express Journal, 2021)
An important advantage of a landscape study is that it illuminates a particular state of nature and conveys the meaning of the weather. Such qualities of the landscape image are achieved by the artist by following the laws of aerial perspective, the method of working with color relationships, finding the right tone and color scheme
Keywords: Landscape; etude; nature; perspective